Dialogical inquiry in practice teaching - Johnsen-Høines, Marit (NOMAD Nordic Studies in Mathematics Education, 2009)
This article refers to a project in which the preconditions for a subject-oriented1, reflective approach towards mathematics and mathematics education in the context of practice teaching were investigated. Student teachers, their tutors and teacher educators participated in the investigation. The article elaborates on their participation as ”co-researchers” in developing the methodological approach and analyses. In addition, the article explores how the analyses provide insight into the didactical conditions for including a subject-oriented approach in practice teaching. More specifically, it was found that practice teaching communication bears the imprint of an evaluative approach that restrains the development of a subject-oriented reflective approach. The conflicting processes characterising these approaches are highlighted.